THE EFFECT OF USING REALIA IN TEACHING WRITING DESCRIPTIVE TEXT ON THE WRITING ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 2 TEBING TINGGI - Dhini Anggraini; Rumiri Aruan; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was aimed to find out whether there was a significant effect of using realia in teaching writing descriptive text on the writing ability of the second year students of SMPN 2 Tebing Tinggi This is a pre-experimental research conducted by using a pre-test, treatment, and post-test. The instrument used in this research was tests (pre-test and post-test) which contained writing activities in describing objects. The population of this research was the Second Year Students of SMPN 2 Tebing Tinggi. The sample of the research was the class VIII.4 which contains 29 students. The needed data were collected by giving test about writing descriptive text (pre-test and post-test) to the students. The collected data were analyzed by using t-test formula. The results of data analysis showed that the mean score of pretest is 29.88, and the mean score of posttest is 63.74 and the difference between the two mean score is 33.85. Besides that, t-test of this research is 25.758 and t-table of this research is 2.048. It means that the t-test score is higher than t-table (25.758>2.048). It can be concluded that there is significant effect of using realia (real objects) in teaching writing descriptive text on the writing ability of the second year students of SMPN 2 Tebing Tinggi. In other words, the alternative hypothesis of this research was accepted. Thus, the use of real objects can be used as media in teaching writing descriptive texts.Key Words: Real Objects, Writing Ability, Descriptive Text